1999
DOI: 10.1007/s003359901180
|View full text |Cite
|
Sign up to set email alerts
|

Re-sequencing of DNA from a diverse panel of cattle reveals a high level of polymorphism in both intron and exon

Abstract: In order to assess the extent of DNA sequence variation in cattle, introns and exons from both the leptin and Amyloid Precursor Protein (APP) genes have been sequenced in a panel of DNAs derived from 22 diverse animals. Direct DNA sequencing of PCR products was used; thus, 44 chromosomes were studied. Polymorphisms were identified by manual scanning of sequence chromatograms and computerized sequence analysis. Twenty Single Nucleotide Polymorphisms (SNPs) were detected in 1788 bp sequenced from the leptin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
37
1
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 12 publications
8
37
1
8
Order By: Relevance
“…A microsatellite has been located in the 5 UTR of the leptin gene [32] and nine SNPs have been discovered in intron 2 of the bovine leptin gene [20,23]. The polymorphisms reported in this study that change the amino acid in exons 2 (Arg/Cys) and 3 (Ala/Val) have been confirmed by Konfortov et al [19], who also report several other intronic polymorphisms in a diverse panel of cattle breeds. Haegeman et al [12] also report the alanine to valine substitution as well as an amino acid change from Glu to Arg in exon 3.…”
Section: Discussionsupporting
confidence: 74%
“…A microsatellite has been located in the 5 UTR of the leptin gene [32] and nine SNPs have been discovered in intron 2 of the bovine leptin gene [20,23]. The polymorphisms reported in this study that change the amino acid in exons 2 (Arg/Cys) and 3 (Ala/Val) have been confirmed by Konfortov et al [19], who also report several other intronic polymorphisms in a diverse panel of cattle breeds. Haegeman et al [12] also report the alanine to valine substitution as well as an amino acid change from Glu to Arg in exon 3.…”
Section: Discussionsupporting
confidence: 74%
“…The T allele frequency was comparatively low in crossbred population as compared to the two pure breeds of taurine cattle, possibly due to the absence of this mutation in Hariana cattle which contributed only the C allele to the crossbred population. Our findings for taurine cattle are similar to those of Buchanan et al (2002) who reported T allele frequencies of 0.58 in Angus cattle, 0.34 in Charolais cattle, 0.55 in Hereford cattle and 0.32 in Simmental cattle (all taurine cattle) and Konfortov et al (1999) who found the T allele frequency to be 0.41 in taurine cattle. In all the four breeds of indicine cattle, the C allele frequency was 1.0, possibly due to the absence of the V allele (valine) in these populations.…”
supporting
confidence: 90%
“…Our results agree with those of Lien et al (1997) who for the first time described a guanine (G) to adenine (A) substitution (G ® A substitution) in intron 2 of the leptin gene of Norwegian cattle. Although Konfortov et al (1999) have reported that some of the B. indicus crossbred cattle have leptin gene polymorphisms that are not found in B. taurus breeds, our findings are the first report of leptin gene polymorphisms in purebred B. indicus cattle. Taken together, the present results suggest that leptin gene mutation might have occurred far back in evolution before the divergence of cattle into taurine (B. taurus) and indicine (B. indicus) cattle.…”
contrasting
confidence: 50%
See 2 more Smart Citations